Systemic lupus erythematosus: diagnosis and management - Tedeschi, Sara K. (Henry Stewart Talks, 2017)
Classification criteria vs. diagnostic criteria, Clinical and laboratory evaluation for suspected SLE, General approach to SLE treatment, Preventive care in SLE, SLE management around the time of pregnancy